PENGARUH SISTEM INFORMASI AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS DALAM MENINGKATKAN PENGENDALIAN INTERNAL PADA KOPERASI WANITA SEJAHTERA - Nando Reza Kurnia Ramadhani; Zaki Bahrun Ni'am (JURNAL CAFETARIA, 2023)
SIA is a system consisting of components used to achieve a company or business organization's goals. A cooperative is a business entity that bases its activities on cooperative principles as well as a movement to build a community economy based on the principle of kinship and members are the highest authority holders at the Annual Member Meeting (RAT). In this study, the data sources used were classified into two, namely primary data and secondary data. The approach in research is descriptive qualitative. To collect information in this study using interviews, field observations, and documentation to determine the process of receiving and disbursing cash at the Prosperous Women's Cooperative in improving internal control. From the results o f the study it was found that prosperous women's cooperatives in cash receipts and disbursements activities still did not fully implement an accounting information system effectively and efficiently.